THE VALIDITY OF INTERACTIVE MULTIMEDIA ON IONIC BOND MATERIAL - Deiya Gama Ilyasa; Kusumawati Dwiningsih (JCER (Journal of Chemistry Education Research), 2019)
Abstract. Interactive multimedia is needed to improve student's understanding of certain material. The purpose of this study is to analyze the validity of interactive multimedia on ionic bonding material. The type of research used in this study is 4P research model (Define, Design, Development, and Dissaminate) but in this study only limited on Development step which adapted from Ibrahim (2014). The validity results showed that: (1) The content validity and construct validity obtained highly valid criteria with average percentage range gradually 90% and 91,04%. From the results, it can be conclude that the developed media was declared valid to be used as interactive multimedia on ionic bond materials.